PROVENANCE OF THE LUTZOW-HOLM COMPLEX, EAST ANTARCTICA-ION MICROPROBE U-Pb STUDY OF ZIRCONS (II) - シライシ, カズユキ; ヒロイ, ヨシクニ; /; モトヨシ, ヨウイチ; ナカイ, ユタカ; SHIRAISHI, Kazuyuki; HIROI, Yoshikuni; ELLIS, D.J.; FANNING, C.M.; MOTOYOSHI, Yoichi; NAKAI, Yutaka (National Institute of Polar Research, 1993)
P(論文) In the sector of 30-45°E in East Antarctica, two high-grade metamorphic complexes, the Lutzow-Holm Complex (LHC) in the east and the Yamato-Belgica Complex (YBC) to the west have been distinguished on the basis of protolith, type of metamorphism and igneous activity. The exact boundary between these complexes has not been established because of the continental ice sheet. Ion microprobe (SHRIMP) dating has been carried out on zircon separates from both meta-sedimentary and meta-igneous rocks of these complexes. U-Pb ages from six widely separated localities throughout the LHC show that the timing of regional metamorphism and folding in the LHC were between ∿520 and ∿555Ma as recorded by new growth of metamorphic zircon. Many zircons contain centers which record a wide range of inherited ages from ∿2900 to ∿1500Ma. ∿1000Ma zircon component has been identified in three locations. ∿1000Ma zircon component may indicate that either the ∿1000Ma adjoining Rayner Complex to the east was a source for the Lutzow-Holm paragneisses or that a similar crustal prehistory is recorded in parts of the LHC. A heterogeneous zircon population in a metasedimentary gneiss from YBC gives a discordant age of ∿2470Ma. Although other analyses from this gneiss do not define unique ages, it is inferred that variable Pb loss at ∿600Ma occurred in zircons that originally crystallized at ∿1000Ma. We have already reported, for the first time, the existence of a Pan-African mobile belt within the East Antarctic Shield (K. SHIRAISHI et al. : Recent Progress in Antarctic Earth Science, ed. by Y. YOSHIDA et al. Tokyo, Terra Sci. Publ., 67,1992). The present work provides additional evidence for an improved fit to the once contiguous fragments of Gondwana. The Highland/Southwestern Complex (HSWC) of Sri Lanka has remarkable petrological similarities to LHC. This metamorphic correlation is now supported by the identification of ∿500Ma age for the LHC, as the Sri Lankan HSWC metamorphism, and folding was also at ∿550-600Ma (A. KRONER ed. : ...